Pola Penggunaan Media Facebook dan TikTok dalam Konteks Kesehatan Mental Remaja pada Siswa Kelas IX SMP Negeri 9 Ambon: Penelitian - Aprilia Tasidjawa; Fatimah Sialana; Herpie Lambiombir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is motivated by the increasing use of social media among adolescents, particularly Facebook and TikTok, which are not only used for entertainment but also influence social relationships and mental health. The aim of this study is to explore how the use of Facebook and TikTok shapes the social interactions of adolescents and its impact on the mental health of ninth-grade students at SMP Negeri 9 Ambon. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with students and Guidance and Counseling (BK) teachers, as well as documentation. The findings show that social media can expand peer networks and serve as a space for self-expression. However, it also has negative effects such as anxiety, fear of negative comments, and social comparison. BK teachers play an important role in providing solutions through personal counseling, digital education, and character development programs. The study concludes that support from both schools and families is essential to help adolescents use social media positively. These findings contribute to a better understanding of the importance of character building amid the challenges of the digital era.